«A Marvellous and Strange Event» Racconti di nascite mostruose nell'Inghilterra della prima età moderna - BARATTA, LUCA (Premio Tesi di Dottorato, 2016)
In early modern England, the birth of a human being with congenital physical deformities was an event which aroused horror and fascination, disgust and morbid curiosity. In a time when modern science was taking its first steps, this kind of prodigy sometimes appeared as a sort of divine punishment for a moral fault, sometimes as a bizarre pastime, or political weapon, or a pre-medical investigation. By deepening such a multifaceted and constantly changing phenomenon, "A Marvellous and Strange Event" tries to build a complex analysis perspective on the English cultural and social history between the 16th and 18th century.